Drinking Water Technologies : A Global Overview (2021)
International experts and veterans have contributed significant information in this book whichencompasses several topics regarding the present pain management problems, and provides the readers with a glimpse into the future of sports nutrition. This book comprises both original research work as well as clinical information categorized under the sections: antioxidant supplementation, herbal/botanical and creatine monohydrate supplementation. The aim of this book is to serve as a valuable source of reference for a broad spectrum of readers including the pain clinicians as well as the common masses.The contamination of various freshwater sources across the world has raised serious doubts the availability and safety of drinking water for a massive population of almost 7.2 billion people.Diarrhoea, cholera, dysentery, typhoid, etc. are some of the common diseases caused by contaminated water. According to WHO 2012 fact sheet, almost 1.8 billion people consume drinking water that is “contaminated with faeces”; and it causes more 500,000 diarrhoeal deaths every year. World Health Organization and most of the developed countries around the world are striving hard to devise novel and innovative methods for purification and distribution of safe drinking water for citizens of this planet. There has been a lot of emphasis lately on researches and studies focusing on diverse substances, pollutants and industrial effluents which will have obvious ramifications for development of new and improved drinking water technologies.This book extensively focuses on the researches that discuss the latest findings and innovations of various drinking water technologies and their effectiveness in treatment of various impurities and contaminants. It also includes case studies and analyses on water distribution and residual management systems. This text is a very significant reference tool for post-graduate students, researchers, scholars and experts.